Study of Resilience in Learning Environments During the Covid-19 Pandemic - Raghunathan, Shriram; Darshan Singh, Abtar; Sharma, Bibhya (Frontiers in Education, 2022)
The Covid-19 pandemic has caused a great change in the world. One aspect of the pandemic is its effect on Educational systems. Educators have had to shift to a pure online based system. This shift has been sudden and without any prior warning. Despite this the Educational system has survived and exhibited resilience. The resilience of a system can be determined if the system continues to operate or function as effectively as before a change. For the domain of education, the Covid-19 pandemic served as a phenomenal change event and a wakeup call to the education fraternity. As a social system, resilience meant that the people in the educational environment continued to function albeit differently. The measure of resilience in education has three major facets – people, the technology which facilitates the process and the process environment. This work aims to understand the resilience of the teachers due to the Covid-19 pandemic, especially how learning continued and what contributed to this continuity. Resilience research and understanding is as important as the pedagogical and technological aspects in an Educational system as it is a trait that encompasses the people, the socio-economic system and their relationships. In this work, we analyzed resilience as trait, its relevance in an Educational system, factors that make up resilience in an Educational system and finally the relevant research about resilience in Education during Covid-19. Based on the results of our literature review we formed a model for Educators. A survey was conducted among educators of 3 countries namely Malaysia, Fiji, and India to determine the essential elements of resilience that were relevant to the continuity of an educational system from the point of view of teachers. We arrived at a set of factors that are relevant to the teachers in the educational systems which can be an impetus for policy makers to focus on and develop.